2016
DOI: 10.1002/ange.201608591
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Trifluoromethylated Ketones from Vinyl Triflates in the Absence of External Trifluoromethyl Sources

Abstract: Anovel method for the conversion of vinyl triflates into a-trifluoromethylated ketones in the absence of external trifluoromethyl sources is described. This process accomplishes an efficient migration of the trifluoromethyl group of the triflate to the a-position in the ketone through ar adical process.T he reaction proceeds by the addition of at rifluoromethyl radical to the vinyl triflate and subsequent fragmentation of the trifluoromethane sulfonyl radical. Based on this reaction, aone-pot two-step procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Evaluation of the reaction conditions Due to the low bond dissociation energy of the O-S bond, enol triflates could undergo desulfurization-fragmentation, followed by formal addition over multiple bonds of enol Article triflates to generate a-trifluoromethylated ketones in a catalytic manifold. 46,48,49 In principle, enol triflates can be divided into three components, namely the trifluoromethyl group, SO 2 , and the ketone moiety. To evaluate the hypothesized switchable use of enol triflate as bifunctional or trifunctional reagents to generate distinct products from the same alkene feedstocks, phenyl enol triflate (1a) was used as a functional reagent and 1-hexene (2a) served as the radical acceptor (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the reaction conditions Due to the low bond dissociation energy of the O-S bond, enol triflates could undergo desulfurization-fragmentation, followed by formal addition over multiple bonds of enol Article triflates to generate a-trifluoromethylated ketones in a catalytic manifold. 46,48,49 In principle, enol triflates can be divided into three components, namely the trifluoromethyl group, SO 2 , and the ketone moiety. To evaluate the hypothesized switchable use of enol triflate as bifunctional or trifunctional reagents to generate distinct products from the same alkene feedstocks, phenyl enol triflate (1a) was used as a functional reagent and 1-hexene (2a) served as the radical acceptor (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, g-trifluoromethylated ketones and trifluoromethylated sulfonyl ketones are important building blocks (Figure 1C). [41][42][43][44][45][46][47] Nonetheless, methods for the synthesis of both types of compounds have been seldomly reported. Herein, a base-controlled reincorporation/release of SO 2 within a photocatalyzed radical difunctionalization of alkenes is described, offering a switchable gateway toward a series of otherwise difficult-to-obtain g-trifluoromethylated ketones and trifluoromethylated sulfonyl ketones (Figure 1B).…”
Section: The Bigger Picturementioning
confidence: 99%
“…Further, the added NHCborane spoiled the default reactionthe α-trifluoromethyl ketone was not formed either. Under Kamimura's conditions 11 (Et 3 B, ambient air, ClCH 2 CH 2 Cl), the α-NHC-boryl ketone 10a was formed, but only in small amounts according to 11 B NMR analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, we soon found that the target reaction proceeded rather smoothly when all the other reagents were replaced by a simple tert-amine (Scheme 1). For example, heating of NHCborane 8, alkenyl triflate 9a (1.3 equiv), and diisopropyl ethyl amine (iPr 2 NEt, 0.8 equiv) in THF at 66 °C for 3 h provided α-NHC-boryl ketone 10a in 66% yield according to 11 B NMR analysis of the reaction mixture. Solvent evaporation and flash chromatography provided pure 10a in 50% yield as a stable white solid.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation